1999
DOI: 10.1021/ja9909172
|View full text |Cite
|
Sign up to set email alerts
|

Hydraphile Channels:  Structural and Fluorescent Probes of Position and Function in a Phospholipid Bilayer

Abstract: Three novel tris(macrocycle)s having fluorescent residues at their distal termini have been prepared and studied. The compounds are of the form 2), and dansyl (3). Compounds 2 and 3 were found to transport Na + at rates similar to those of other tris(macrocyclic)s but 1 was not an ionophore in the bilayer as assessed by 23 Na NMR analysis. The latter failure may be due to a hydrogen-bond blockade leading to a globular conformation adopted by the hydraphile. The fluorescence maximum of 3 was determined in a var… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
53
0

Year Published

2003
2003
2023
2023

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 70 publications
(54 citation statements)
references
References 65 publications
1
53
0
Order By: Relevance
“…The dansyl residue of 13 absorbs light at this wavelength and fluoresces at λ = 516 nm. This fluorescence resonance energy transfer (FRET) experiment indicates that at least for these two compounds, the aggregation number is 1.1 [59]. This supports the initial unimolecular design criteria.…”
Section: Defining the Conformation In The Bilayersupporting
confidence: 66%
See 1 more Smart Citation
“…The dansyl residue of 13 absorbs light at this wavelength and fluoresces at λ = 516 nm. This fluorescence resonance energy transfer (FRET) experiment indicates that at least for these two compounds, the aggregation number is 1.1 [59]. This supports the initial unimolecular design criteria.…”
Section: Defining the Conformation In The Bilayersupporting
confidence: 66%
“…The fluorescence maximum for 13 was measured when the channel was in the membrane. Its shift suggested that it experienced an environment similar to but slightly more polar than ethanol [59]. If the tris(macrocycle) portion of the molecule spans the insulator regime and the dansyl groups are in the midpolar regime, the observed polarity is as expected.…”
Section: Defining the Conformation In The Bilayermentioning
confidence: 78%
“…28 We reported that the dansyl headgroup of 7 experienced a local dielectric similar to that expected for the midpolar regime of the bilayer. 29 The latter measurements were confirmed using fluorescence depth quenching.…”
Section: Dansyl Fluorescence Emission Spectramentioning
confidence: 58%
“…36, 37 When R in the structure of Scheme 3 is 3-indolylmethyl, the channel fails to transport cations. 38 It seems unlikely that protonation of the indole nitrogen is an issue, as its pK A is about 2.3. 39 Further, the six aliphatic nitrogen atoms are more basic and will certainly protonate first.…”
Section: Meisel Jw Et Al: Synthetic Antimicrobial J Explor Res Pharmmentioning
confidence: 99%